Treasury's Forecasting Performance: A Head-to-Head Comparison - Khoon Lek Goh; Daniel Lawrence (New Zealand Government, The Treasury, 2006)
Work on assessing Treasury's forecasting performance to date has focussed on comparisons against consensus forecasts. This study compares Treasury's GDP and CPI forecast performance against individual private sector forecasters as well as major public sector institutions such as the IMF, OECD and the Reserve Bank of New Zealand. The head-to-head comparison makes it possible to assess Treasury's forecasting performance relative to its peers. When compared across all evaluation periods covering 1996-2005, Treasury's GDP forecast performance was ranked in the middle at seventh out of 16. The large forecast error for the 1998 year had a material impact on Treasury's overall forecast performance. Treasury's CPI forecast performance was not as good, placing tenth out of 12. Large forecast errors for the 1998-2000 period accounted for the poor CPI forecast performance. Treasury's overall forecast performance was better when evaluating only the current year Budget forecasts, placing fourth for GDP and sixth for CPI. This suggests that Treasury is better at forecasting the current year than the year ahead. Consistent with international studies, no single forecaster consistently outperforms the Consensus, with Treasury beating the Mean 30% of the time for GDP and Consensus 33% of the time for CPI. All forecasters find it difficult to pick recessions and turning points. Large forecasting groups generally have a poorer forecasting record on average.
Keywords: E27; E37; 330; Forecast accuracy; New Zealand